Motivation, Identity, and Emergence of Self: ESL Learners in Bridge Course at Aligarh Muslim University - Shagufta Imtiaz; Anam Shams; Mirza Adam (Talenta Publisher, 2021)
The study aims at viewing the second language learners enrolled in the Bridge Course of English, at Aligarh Muslim University (AMU). The Bridge Course is of a year’s duration and the objective is to prepare the learner with ‘institutionalised supplement education and wider employment avenues’. This is done with the aim to mainstream the ESL learners who have Urdu as their mother tongue and have learned Arabic as a foreign language in Madarsa. Their need to learn a second foreign language, which is the global English, has been explored from the perspective of motivation and identity. The study attempts to probe into the dimensions of identity and emergence of self among learners. It has been substantiated with quantitative and qualitative analysis by using SPSS version 17 software and one way ANOVA univariate test. The findings suggest that, compared to the learners’ having only instrumental motivation towards the target language, their possession of both integrative and instrumental motivation in line with their ideal self and ought-to self were invested more into the learning of target language.